Not all fun and games: videogame labour, project-based workplaces, and the new citizenship at work - Milburn, Trudy (Journal of Broadcasting & Electronic Media, 2025)
Keywords: Citizenship; Engineering; Law; Political science; Public relations; Sociology; Work (physics); dept.aa

Early college program implementation and growth: a collaborative initiative by a state university - Yavuz, Olcay; Milburn, Trudy (Concurrent Enrollment Review, 2025)
This article explores a collaborative initiative undertaken by a state university aimed at implementing and expanding an Early College Program. The conceptual framework, practical strategies, collaborative efforts and background of this initiative are presented. With a focus on improving college access for all, the article introduces the university's efforts to promote an inclusive Early College Program accessible to high-need students in particular. This collaborative approach highlights the importance of fostering collaboration among both internal and external partners of Institutions of Higher Education (IHE). By sharing insights into the program design and implementation, the article aims to inspire similar initiatives and contribute to the ongoing dialogue promoting early college experiences for all.
Keywords: Conceptual framework; Focus (optics); Focus group; Higher education; Program evaluation; State (computer science); dept.aa; dept.edl

Organizational communication scholars and U.S. higher education leadership: opportunities and challenges when scholars become administrators - Castor, Theresa; Milburn, Trudy; Eisenberg, Eric M.; Shockley-Zalabak, Pam (Management Communication Quarterly, 2025)
Universities and colleges are organizations that significantly impact students, their communities, and society. This forum explores how organizational communication scholars who are university leaders have applied their scholarly backgrounds to inform their roles. The forum participants engage in the work of being reflective practitioners to shed light on how organizational communication theory can help in negotiating the everyday lived experience of academic leadership. Three key issues are explored: (1) in what ways are organizational communication scholars uniquely positioned to assume a university leadership role? (2) how do communication concepts inform the communication practices of administrators? and (3) how do communication practices contribute to universities as multi-faceted institutions? The participants conclude by reflecting on current challenges in higher education and the potential of organizational communication scholars to play a vital role in navigating those challenges.
Keywords: dept.aa; peer-reviewed